2019
DOI: 10.1136/bmjopen-2018-025213
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Hikikomori’ syndrome: worldwide prevalence and co-occurring major psychiatric disorders: a systematic review and meta-analysis protocol

Abstract: IntroductionThe ‘Hikikomori’ syndrome (HS) consists of prolonged and severe social withdrawal. It has been studied first in Japan and recently has increasingly drawn the attention of researchers and clinicians all over the world. It is unclear whether it exists in other cultural contexts than Asia. The existing systematic reviews did not provide a quantitative synthesis on its prevalence. In addition, a summary of the co-occurring rates of psychiatric disorders is lacking. To provide a more comprehensive under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 47 publications
1
36
0
1
Order By: Relevance
“…As in our previous meta-analytical works,11 45 the Newcastle-Ottawa Quality Assessment Scale (NOS) will be adopted by two independent meta-analysts to examine the methodological quality of each study 46. This checklist is based on a maximum score of nine: four points are assigned to inclusion criteria of cases and controls (definition of cases, selection of cases, definition of control subjects, selection of control subjects), two points are assigned to the comparability criteria of cases and control subjects according to study design and statistical analysis (comparability in terms of age and gender), and three points to exposure verification criteria of cases and control subjects (exposure verification, same method of verification, no response point).…”
Section: Methodsmentioning
confidence: 99%
“…As in our previous meta-analytical works,11 45 the Newcastle-Ottawa Quality Assessment Scale (NOS) will be adopted by two independent meta-analysts to examine the methodological quality of each study 46. This checklist is based on a maximum score of nine: four points are assigned to inclusion criteria of cases and controls (definition of cases, selection of cases, definition of control subjects, selection of control subjects), two points are assigned to the comparability criteria of cases and control subjects according to study design and statistical analysis (comparability in terms of age and gender), and three points to exposure verification criteria of cases and control subjects (exposure verification, same method of verification, no response point).…”
Section: Methodsmentioning
confidence: 99%
“…The term hikikomori describes individuals who have withdrawn from their community. 3 The initial reports emphasized the close relation of the clinical manifestation with the local culture, as suggested by the name, which is a compound Japanese word made of 2 verbs indicating the attitude of an individual "to pull back" (hiku) and "to selfseclude" (komoru). 6 However, increasing reports from around the world provided a better understanding of this condition and suggested that hikikomori is a global health problem, which may exist as an independent primary diagnosis.…”
Section: Definition Of the Hikikomori Disordermentioning
confidence: 99%
“…13 Hikikomori could be considered a new primary psychiatric disorder in future versions of the Diagnostic and Statistical Manual of Mental Disorders, despite the presence of some clinical overlap with other mental disorders. 3,14 Published reports have clarified the pathologic features of hikikomori, and have built a consensus regarding its clinical characteristics, complications, and management. 13 Individuals with hikikomori present a severe social isolation characterized by a marked physical self-inflicted seclusion in their home.…”
Section: Definition Of the Hikikomori Disordermentioning
confidence: 99%
See 2 more Smart Citations